Influential Variables in the Choice between Roads and Railways for General Foreign Trade Cargo - Pineda Jaramillo, Juan Diego; Sarmiento, Iván (Ingeniería Solidaria, 2014)
Although cargo transport by road involves many difficulties in Colombia, there is no existing study showing the variables that influence the choice of a cargo transport modality, to determine whether or not a railway would truly be useful in a particular region. In this study, a qualitative investigation is performed using focus group techniques among important companies of a region, illustrating the methodology with the case of Antioquia; in this manner, the variables that influence the choice of transport modality by companies that export and import merchandise are determined. These variables will be important for future works when estimating demand.
Keywords: railway transport; foreign trade; declared preferences; cargo transport